Análisis de los contenidos audiovisuales asiáticos en la audencia juvenil en la Provincia de Los Ríos - Pin Anchundia, Isis Mercedes (2020)
The current research work was aimed at enhancing an approach to young people in the province of Los Ríos in order to determine the influence of Asian audiovisual content on them, and see what content attracts their most attention. In order to meet the objective of this research, it was done through the interview and the survey, for this reason the research resulted in being mixed (quantitative and qualitative) due to the fact that it is the data collection tool that were used to obtain the results. In this way, it was possible to observe the degree of interest of young people about Asian audiovisual content, a graph was made to see the result of the questions, to be able to make the conclusions that positively or negatively support what was established. The interviewees and respondents were able to provide remarkable information to be able to carry out this research project, so the level of influence that exists in the young people of the Los Ríos province in cantons such as Baba, Babahoyo, Buena fe, Vinces, Mocache, Buena fe, Palenque, Montalvo, Puebloviejo, Quevedo, Quinsaloma, Urdaneta, Valencia, Ventana’s, At the end of this research with its analysis and interpretation of the results achieved, it was concluded that young people do feel influenced by the culture of these countries since through their contents they can appreciate and learn from their culture, and although there are not many the hours they dedicate if you learn from these trends since they consume you all week.